Le contrat sexuel - Pateman, Carole (La Découverte Poche, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »-- Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Réflexions autour de la notion d’homophobie: succès politique, malaises conceptuels et application empirique - Chamberland, Line; Lebreton, Christelle (Nouvelles Questions Féministes, 2012)
Après en avoir retracé rapidement la genèse, cet article rapporte les principales critiques adressées au concept d’homophobie, notamment son réductionnisme qui tend vers des explications de nature psychologique ainsi que l’éviction de la hiérarchie des sexes/genres. Nous discutons ensuite deux pistes théoriques permettant de contourner les limites précédemment identifiées. La première examine le potentiel de l’approche intersectionnelle. La seconde voie invite à une redéfinition du concept d’homophobie, lui reconnaissant une portée exclusivement descriptive, et non plus en tant que concept explicatif, justifiant ainsi sa subordination au concept d’hétérosexisme qui offre une perspective systémique. Nous examinons ces concepts en fonction de leur capacité à rendre compte de l’oppression des lesbiennes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Ces corps qui comptent : de la matérialité et des limites discursives du sexe - Butler, Judith (Éditions Amsterdam, 2009)
Traduction de Bodies That Matter, (1993) La prise en compte de la matérialité des corps n’implique pas la saisie d’une réalité pure, naturelle, derrière le genre : si le sexe est un présupposé nécessaire du genre, nous n’aurons jamais accès au réel du sexe qu’à travers nos schèmes culturels. Le sexe, comme le genre, est une norme culturelle, qui régit la matérialité des corps. Il importe donc de souligner que le concept de matière a une histoire, où sont sédimentés les discours sur la différence sexuelle. En outre, si certains corps (par exemple blancs, mâles et hétérosexuels) sont valorisés par la norme, d’autres (par exemple lesbiens ou non blancs) sont produits comme abjects, rejetés dans un dehors invivable. À travers une reprise critique du concept foucaldien de « contrainte productive », Judith Butler s’efforce, loin de tout volontarisme, de ressaisir la façon dont ces corps peuvent défaire les normes qui les constituent et devenir le lieu d’une puissance d’agir transformatrice. Ce livre, où l’épistémologie se mêle à la politique, constitue un jalon des études de genre et l’un des ouvrages majeurs de son auteure.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; art contemporain; corps; cours; culture; discipline; fem1000; genre; hétérosexisme; identités LGBTQIA2+; lit4700; maternité; philosophie; pol4212; politique; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe; soc2014; systèmes d'oppressions; thématiques; épistémologie; épistémologie queer; états-unis; études culturelles

Qu'est-ce que le care?: souci des autres, sensibilité, responsabilité - Molinier, Pascale; Laugier, Sandra; Paperman, Patricia (Petite bibliothèque Payot, 2009)
"Apporter une réponse concrète aux besoins des autres, telle est, aujourd'hui, la définition du care, ce concept qui ne relève pas, comme on l'a longtemps cru, du seul souci des autres ni d'une préoccupation spécifiquement féminine, mais d'une question politique cruciale recoupant l'expérience quotidienne de la plupart d'entre nous. Première synthèse sur cette notion d'une très grande ampleur après les travaux fondateurs de Carol Gilligan dans les années 1980 puis de Joan Tronto dans les années 1990, ce livre concerne aussi bien le domaine du travail que ceux du genre, de l'éthique et de la santé."
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail du care

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Le genre, structure sérielle : penser les femmes comme un groupe social - Young, Iris Marion (Recherches féministes, 2007)
À la suite des critiques formulées par des femmes de couleur et par des lesbiennes quant à la conception ethnocentrique blanche et hétérosexiste d’une bonne partie de la réflexion féministe, l’auteure essaie de penser la catégorie « femmes » en dehors des définitions essentialisantes et totalisantes. Elle propose, à cette fin, de recourir à la notion sartrienne de structure sérielle pour penser les femmes comme un groupe social dont les membres n’ont pas nécessairement à partager les mêmes attributs. Cela lui permet d’envisager la possibilité d’un féminisme qui ne repose pas sur la catégorie « femmes » dans son ensemble, mais qui émerge plutôt des pratiques, nécessairement parcellaires, de femmes qui transforment en enjeux politiques certains aspects de la « condition féminine ». Ainsi, il devient possible de penser le féminisme comme théorie et pratique politiques sans le faire procéder de « femmes » dont la condition serait identique en tous points, mais plutôt de coalitions qui remettent en cause un aspect particulier des rapports de pouvoir entre hommes et femmes. Taking into consideration critiques from women of color or lesbians on the white ethnocentric and heterosexist character of a large part of feminist theorizing, I try to conceptualize the category “women” while avoiding both essentialism and totalisation. For this purpose, I propose to use the Sartrian concept of seriality in order to think about women as a social group, without implying that all women share a set of social attributes. This allows me to adopt a conception of feminism that does not proceed from the category “women” as a whole, but stems out of the partial practices that politicize various aspects of “women’s condition”. Thus, one can define feminism as a theory and a political practice that is not exclusive to the domain of “women”, but rather draw on various coalitions that challenge the power relation between men and women in some respect.
Keywords: 1900-1999; 1990-1999; amériques; cours; discipline; fem1000; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories féministes; états-unis

« La réflexion queer : apports et limites ». Dans Dialogues sur la troisième vague féministe - Mensah, Maria Nengeh; Lamoureux, Diane (Dialogues sur la troisième vague féministe, 2005)
Dialogues sur la troisième vague féministe rassemble des voix qui, chacune à sa manière, propose des pistes de réflexion quant à la nature des changements qui affectent le féminisme québécois. Ces dialogues explorent des thématiques liées au pouvoir, à la sexualité et à l'image du corps, liées à la mondialisation, aux conflits générationnels, au backlash, et à la relation entre la théorie, la pratique et la culture populaire
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; identités LGBTQIA2+; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; troisième vague

La citoyenneté multiculturelle: une théorie libérale du droit des minorités - Kymlicka, Will (Éditions La Découverte ; Éditions du Boréal, 2001)
Les sociétés contemporaines deviennent de plus en plus des sociétés multiculturelles dans lesquelles les groupes minoritaires ethniques ou nationaux réclament une reconnaissance publique et les moyens de préserver leur identité culturelle. Une revendication qui n'est pas sans susciter des conflits qui menacent parfois l'unité territoriale des États. Pour Will Kymlicka, la réponse à cet enjeu devenu incontournable constitue aujourd'hui l'un des plus grands défis pour la démocratie. Son propos, dans ce livre devenu un classique de la théorie politique, est de défendre une nouvelle conception du statut et des droits des minorités culturelles.
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; citoyenneté; cours; discipline; discours dominant; europe; histoire et politique; inégalités; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

« Penser le sexe: pour une théorie radicale de la politique de la sexualité». Dans Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (Marché au sexe, 2001)
Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; europe; homophobie; hétérosexualité; identités LGBTQIA2+; lesbianisme; occident; phi2030; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc2014; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Excitable speech: A politics of the performance - Butler, Judith (Routledge, 1997)
‘When we claim to have been injured by language, what kind of claim do we make?’ - Judith Butler, Excitable Speech Excitable Speech is widely hailed as a tour de force and one of Judith Butler’s most important books. Examining in turn debates about hate speech, pornography and gayness within the US military, Butler argues that words can wound and linguistic violence is its own kind of violence. Yet she also argues that speech is ‘excitable’ and fluid, because its effects often are beyond the control of the speaker, shaped by fantasy, context and power structures. In a novel and courageous move, she urges caution concerning the use of legislation to restrict and censor speech, especially in cases where injurious language is taken up by aesthetic practices to diminish and oppose the injury, such as in rap and popular music. Although speech can insult and demean, it is also a form of recognition and may be used to talk back; injurious speech can reinforce power structures, but it can also repeat power in ways that separate language from its injurious power. Skillfully showing how language’s oppositional power resides in its insubordinate and dynamic nature and its capacity to appropriate and defuse words that usually wound, Butler also seeks to account for why some clearly hateful speech is taken to be iconic of free speech, while other forms are more easily submitted to censorship. In light of current debates between advocates of freedom of speech and ‘no platform’ and cancel culture, the message of Excitable Speech remains more relevant now than ever.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; performativité; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; états-unis

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Thinking gender, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Feminism/postmodernism - Nicholson, Linda J. (Thinking gender, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis

Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis